2013
DOI: 10.1111/jasp.12175
|View full text |Cite
|
Sign up to set email alerts
|

Inspiring altruism: reflecting on the personal relevance of emotionally evocative prosocial media characters

Abstract: Educators have proposed that admired behavior by media characters evokes audience emulation if subsequent personal reflection results in audience members realizing that they want to and are able to behave in a similar manner. Two experiments investigated this. In Study 1, exposure to prosocial media models increased altruistic inclinations among teenagers only if they were also instructed to reflect on the personal significance of what they had seen. In Study 2, medical students exposed to prosocial media mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…In addition to the moderators included in the current meta-analysis, there are a number of other moderators that have been proposed and demonstrated in the prosocial modeling literature. Some were contextual variables, including a low versus high cost of helping (Olivola & Shafir, 2018; Wagner & Wheeler, 1969), low versus high need for help (Wagner & Wheeler, 1969; Solomon & Grota, 1976), cooperative versus competitive social context (Masor, Hornstein, & Tobin, 1973), model competence (Eisenberg-Berg & Geisheker, 1979), and an opportunity for personal reflection of the modeled behavior (Farsides, Pettman, & Tourle, 2013). Some proposed moderators included individual differences, such as safety versus esteem orientation (Wilson, 1976), social dominance orientation (Freeman, Aquino, & McFerran, 2009), and prosocial orientation (Gentile et al, 2009).…”
Section: Moderators Of the Prosocial Modeling Effectmentioning
confidence: 99%
“…In addition to the moderators included in the current meta-analysis, there are a number of other moderators that have been proposed and demonstrated in the prosocial modeling literature. Some were contextual variables, including a low versus high cost of helping (Olivola & Shafir, 2018; Wagner & Wheeler, 1969), low versus high need for help (Wagner & Wheeler, 1969; Solomon & Grota, 1976), cooperative versus competitive social context (Masor, Hornstein, & Tobin, 1973), model competence (Eisenberg-Berg & Geisheker, 1979), and an opportunity for personal reflection of the modeled behavior (Farsides, Pettman, & Tourle, 2013). Some proposed moderators included individual differences, such as safety versus esteem orientation (Wilson, 1976), social dominance orientation (Freeman, Aquino, & McFerran, 2009), and prosocial orientation (Gentile et al, 2009).…”
Section: Moderators Of the Prosocial Modeling Effectmentioning
confidence: 99%
“…For Class 4 populations, policies should strengthen and increase adherence to altruistic values, self-perceptions, and behaviors. Increasing altruism nudges (e.g., making altruism norms salient) and fostering habits of personal reflection on altruism (e.g., questions on the importance/consequences of altruism) are directions that may strengthen the enforcement mechanism between altruistic self-perception and behaviors ( Farsides et al, 2013 ; Capraro et al, 2019 ). While applicable to Class 3 populations, increasing accessibility and engagement to altruistic behaviors is the foremost priority for this population and may be achieved by targeting the interests/preferences for altruism within this population profile.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that there is a strong effect with well-known media characters, which viewers tend to identify with and imitate (Calvert, Murray, & Conger, 2004), and it is easy for individuals to predict a game character's behavior and behave similarly when playing a famous role (Bargh, Chen, & Burrows, 1996). On the other hand, prosocial media characters (e.g., justice behavior) can evoke altruism emotionally in children (Farsides, Pettman, & Tourle, 2013;Funk, Baldacci, Pasold, & Baumgardner, 2004). Given that the pretest levels of aggression were not signi cant between treatment group and the control group, it can be concluded that watching prosocial cartoons (versus nonprosocial) leads to lower level of aggression.…”
Section: Repeated Exposure To Prosocial Cartoons Reduces Aggression Over Timementioning
confidence: 99%